Analisis Kemampuan Pemecahan Masalah Matematis : Dampak Metode Drill ditinjau dari Gaya Belajar - Fransiska, Cici; Masykur, Ruhban; Putra, Fredi Ganda (Desimal: Jurnal Matematika, 2019)
This study aims to determine the differences in the Drill method of mathematical problem solving abilities of participants, differences in students with visual, auditory or kinesthetic learning styles on problem solving abilities and interactions between learning methods and learners' learning styles on mathematical problem solving abilities. The method used is the Quasy Experiment method, this study uses analysis of variance (ANAVA) two ways with unequal cells. Data collection techniques are carried out by observation, interviews, documentation and questionnaire methods. The results showed that there were differences in the Drill Method towards students 'mathematical problem solving abilities, there was no difference in visual, auditory and kinesthetic learning styles towards mathematical problem solving abilities and there was no interaction between learning methods and learners' learning styles towards mathematical problem solving abilities, p. this is because learning methods (Drill methods and direct learning) and learning styles of students have the same effect on mathematical problem solving abilities.